Patellar tendon elastic properties derived from in vivo loading and kinematics. (April 2023) - Kneifel, Paul; Moewis, Philippe; Damm, Philipp; Schütz, Pascal; Dymke, Jörn; Taylor, William R.; Duda, Georg N.; Trepczynski, Adam
Abstract: Patellar complications frequently limit the success of total knee arthroplasty. In addition to the musculoskeletal forces themselves, patellar tendon elastic properties are essential for driving patellar loading. Elastic properties reported in the literature exhibit high variability and appear to differ according to the methodologies used. Specifically in total knee arthroplasty patients, only limited knowledge exists on in vivo elastic properties and their corresponding loads. For the first time, we report stiffness, Young's modulus, and forces of the patellar tendon, derived from four patients with telemetric total knee arthroplasties using a combined imaging and measurement approach. To achieve this, synchronous in vivo telemetric assessment of tibio-femoral contact forces and fluoroscopic assessment of knee kinematics, along with full body motion capture and ground reaction forces, fed musculoskeletal multi-body models to quantify patellar tendon loading and elongation. Mechanical patellar tendon properties were calculated during a squat and a sit-stand-sit activity, with resulting tendon stiffness and Young's modulus ranging from 511 to 1166 N/mm and 259 to 504 MPa, respectively. During these activities, the patellar tendon force reached peak values between 1.31 and 2.79 bodyweight, reaching levels of just ∼0.5 bodyweight below the tibio-femoral forces. The results of this study provide valuable input data for mechanical simulations of the patellar tendon and the whole resurfaced knee.